Le territoire comme lieu privilegie de transmission des savoirs et des valeurs des femmes Atikamekw - Basile, Suzy; Asselin, Hugo; Martin, Thibault (Recherches Feministes, 2017)
L’analyse thématique de 32 entrevues réalisées avec des femmes Atikamekw révèle qu’elles connaissent le mode de vie de leurs ancêtres et le rôle que les femmes y jouaient, que ce rôle était prédominant et essentiel dans l’organisation spatiale des activités traditionnelles sur le territoire, que les accouchements sont des marqueurs spatiotemporels, que la désignation du lieu d’origine a changé à la suite des bouleversements sociaux et territoriaux, que la désignation des personnes par le nom traditionnel est toujours en usage, que les femmes Atikamekw étaient responsables de l’éducation. L’obligation d’envoyer les enfants dans les pensionnats de 1955 à 1972 a provoqué une cassure dans la transmission des savoirs sur le territoire et les différentes formes de colonisation ont érodé peu à peu l’influence des femmes.
Keywords: amériques; approches et analyses; canada; care; corps; cours; féminisme autochtone; histoire et politique; intersectionnalité; justice reproductive; justice sociale; maternité; nation Atikamekw; pensionnats; pol4105; premier cycle; québec; régions géographiques; système colonial; systèmes d'oppressions; thématiques; transmissions; violences; éducation

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

À la rencontre des femmes Autochtones du Québec - Larivière, Widia; Boulanger, Sébastien; Champagne, Julie; Dubois, Christian; Bouchard, Sylvie; Québec (Province). Conseil du statut de la femme (Conseil du statut de la femme, 2016)
L’organisme Femmes Autochtones du Québec et le Conseil du statut de la femme ont uni leur expertise pour mettre en lumière la réalité des femmes autochtones du Québec. Les femmes autochtones et les femmes non autochtones ont une histoire qui leur est propre, des origines différentes et une identité distincte, ce qui ne les empêche pas de nouer des partenariats1 et de nourrir des aspirations communes. Comme par exemple valoriser la parole et l’action des femmes, souhaiter l’autodétermination et la nondiscrimination pour toutes.
Section: 53 pages : illustrations en couleur ; 28 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; droits des femmes*; féminisme autochtone; histoire et politique; justice reproductive; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail; violences; éducation

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

The winter we danced: voices from the past, the future, and the Idle No More movement - Kino-nda-niimi Collective (ARP Books, 2014)
"The Winter We Danced is a vivid collection of writing, poetry, lyrics, art and images from the many diverse voices that make up the past, present, and future of the Idle No More movement. Calling for pathways into healthy, just, equitable and sustainable communities while drawing on a wide-ranging body of narratives, journalism, editorials and creative pieces, this collection consolidates some of the most powerful, creative and insightful moments from the winter we danced and gestures towards next steps in an on-going movement for justice and Indigenous self-determination"
Section: 439 pages : illustrations (certaines en couleur) ; 22 cm
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; canada; care; cours; créativité; discipline; féminisme autochtone; images; justice sociale; militance; musique; pol4105; poésie; premier cycle; périodes historiques; régions géographiques; santé; thématiques; études littéraires

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Un protocole d'application culturellement pertinent selon les sexes - Association des femmes autochtones du Canada (AFAC) (2011)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; pol4105; premier cycle; périodes historiques; québec; régions géographiques; santé; santé mentale; sciences humaines; sciences sociales; suicide; système colonial; systèmes d'oppressions; thématiques; traumatismes générationnels; travail social; violences

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis

La grand-maternité chez les Inuits Portrait d’une réalité méconnue - Sigouin, Catherine; Charpentier, Michèle; Quéniart, Anne (Nouvelles pratiques sociales, 2011)
Cet article explore la grand-maternité telle qu’elle est construite et vécue chez les Inuits du Nunavik, à partir d’une recension de la littérature ainsi que des résultats préliminaires d’une recherche qualitative visant à connaître le point de vue des grands-mères inuites sur leur place et leurs rôles au sein de la famille. L’étude met notamment en lumière la place centrale et indispensable des grands-mères dans les soins et l’éducation des petits-enfants. Elle soulève également certains questionnements quant à la pertinence des programmes psychosociaux actuellement en place. Ces observations tendent en faveur d’une reconnaissance du rôle essentiel des grands-mères inuites à travers la mise en place de programmes et de services mieux adaptés à cette clientèle.
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; féminisme autochtone; féminisme décolonial; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; travail social; trs1205